Optimal indication of thyroglobulin measurement in fine‐needle aspiration for detecting lateral metastatic lymph nodes in patients with papillary thyroid carcinoma. Issue 6 (1st August 2013) - Chung, Jin; Kim, Eun Kyung; Lim, Hyunsun; Son, Eun Ju; Yoon, Jung Hyun; Youk, Ji Hyun; Kim, Jeong‐Ah; Moon, Hee Jung; Kwak, Jin Young
Abstract Background The purpose of this study was to evaluate optimal indication of thyroglobulin (Tg) measurement in fine‐needle aspiration (FNA) for detecting lateral metastatic lymph nodes in patients with papillary thyroid carcinoma (PTC). Methods We performed a retrospective study of 241 lymph nodes of 220 patients who underwent ultrasound‐guided FNA with Tg in FNA (FNA‐Tg) washout fluid measurements for suspicious lymph nodes. Results On multivariate analysis, hyperechogenicity, cystic change, presence of calcifications, and peripheral vascularity were independent factors predictive of lymph node metastasis. After adding FNA‐Tg, sensitivity and accuracy were significantly increased when the lymph node had 1 or 2 suspicious ultrasound features. However, sensitivity and accuracy were not significantly increased when the lymph node had multiple suspicious ultrasound features. Conclusion Additional FNA‐Tg can help diagnose a metastatic lymph node with 1 or 2 suspicious ultrasound features. However, additional FNA‐Tg is not beneficial in lymph nodes with highly suspicious ultrasound features, in which FNA alone is sufficient for diagnosis of predictive of lymph node. © 2013 Wiley Periodicals, Inc. Head Neck 36: 795–801, 2014